Future of Electric vehicles: Empirical study in relations to Potential Factors - Dr. Sunita Pachar, Dr. Shaifali Garg (International Journal of Advanced Science and Technology, 2020)
AbstractElectric vehicles future will be different from today as like the initially automobiles differed from buggies; Primary focus of the paper is to find the potential factors that somewhere affect the sale of electric vehicles. Recent studies from the university and KPMG predict that the arrival of autonomous vehicles will reduce private car ownership in the united states by 43 percent by 2030 and sales in urban markets by 50 percents by 2035, similarly in India the electric vehicles market made big gains in 2019 across multiple car manufacturers and the industry has ever bigger plans for the years to come. This paper explore that there are several problem associated with the consumer awareness towards the products being marketed which includes the demographic factors, such as age, gender, education level, population belongingness. Other factors such as improper advertisement, communication barrier, reach to the last person is also plays a major role in consumer awarensss about a product.